Equine infectious anemia virus tat: insights into the structure, function, and evolution of lentivirus trans-activator proteins. - Dorn, P (1990)
Equine infectious anemia virus (EIAV) contains a tat gene which is closely related to the trans-activator genes of the human and simian immunodeficiency viruses. Nucleotide sequence analysis of EIAV cDNA clones revealed that the tat mRNA is composed of three exons; the first two encode Tat and the third may encode a Rev protein. Interestingly, EIAV Tat translation is initiated at a non-AUG codon in exon 1 of the mRNA, perhaps allowing an additional level of gene regulation. The deduced amino acid sequence of EIAV tat, combined with functional analyses of tat cDNAs in transfected cells, has provided some unique insights into the domain structure of Tat. EIAV Tat has a C-terminal basic domain and a highly conserved 16-amino-acid core domain, but not the cysteine-rich region, that are present in the primate immunodeficiency virus Tat proteins. Thus, EIAV encodes a relatively simple version of this kind of trans activator.